FAKTOR-FAKTOR PENYEBAB TERJADINYA PENYAKIT OSTEOPOROSIS PADA LANSIA DI UPT PELAYANAN SOSIAL LANJUT USIA DI WILAYAH BINJAI TAHUN 2017 - Leny Suarni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Osteoporosis is a disease that attacks the bone where the bone becomes brittle (flagella) and is easily broken and fractured. Many of the factors that cause Osteopororsis are one of them is calcium deficiency, especially in childhood to adolescence. By looking at the conditions above, the writer wants to do a research that aims to find out the Factors Causing Osteoporosis in the Elderly in the 2017 Binjai Elderly Service Unit. This research is descriptive with a cross sectional design carried out for the elderly with 25 people. This data collection is done by questionnaire. The results of this study indicate that the factors that cause osteoporosis are calcium deficiency factors as many as 18 people (72%), drug factors as many as 20 people (80%), smoking factors and consuming alcohol as many as 10 people (40%), factors lack of exercise as many as 19 people (76%), and disease factors as many as 15 people (60%). So, it can be concluded that the most dominant cause of osteoporosis in the elderly in the UPT for Elderly Social Services in the Binjai Region in 2017 is 80% Medicines. Therefore, it is expected that the elderly will consume less drugs that can cause Osteoporosis.Keywords: Osteoporosis, Causes of Osteoporosis, Elderly